The Reality of Applying The Dimensions of The Quality of Service of Higher Education and its Impact on The Development of Organizational Commitment: A Survey Study of a Sample of The Teaching of the University of Kirkuk - Khazaal, Baser (Finance and Business Economies Review, 2019)
Testified last year's great interest in adopting the dimensions of service quality in educational institutions, which is reflected on their commitment to their organization's commitment to the institution and their direction, hence the study aimed to measure and analyze the impact of the link and relationship between the dimensions of quality of service and of b (tangibility, reliability, responsiveness, safety, and emotional) as independent variables and (organizational commitment) as a dependent variable, as well as the discovery of the amount of variation in the effect of dimensional referred to in the organizational commitment to development among faculty members. I have been using the questionnaire form as a tool to collect study data and to achieve their goals of definition The study variables and the nature of their relationship, was the University of Kirkuk, a field of study. The study found a number of conclusions notably that the dimensions of service quality are linked and affect moral commitment to organizational, and under some proposals that will contribute to draw the attention of the administrative leaders of the colleges surveyed to identify the roles of these dimensions and the search for the most important mechanisms and means to be adopted has offered being an important dimension to the development of organizational commitment of faculty members as the cornerstones of the educational process so it has to be attention to this aspect